2019
DOI: 10.1007/s00595-019-01839-0
|View full text |Cite
|
Sign up to set email alerts
|

Is laparoscopic colorectal surgery with continuation of antiplatelet therapy safe without increasing bleeding complications?

Abstract: PurposeThe number of patients on antiplatelet therapy (APT) who need surgery is increasing; however, it is unclear whether APT should be continued for abdominal surgery, particularly laparoscopic colorectal surgery. We investigated the safety of continuing APT for patients undergoing laparoscopic colorectal surgery.MethodsWe collected retrospective data from 529 patients who underwent laparoscopic colorectal surgery at Hiroshima University between January, 2013 and December, 2018. We analyzed information relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Even though these procedures were in the same intermediate risk group, they could not be said to have the same bleeding risk. In addition, other previous studies on whether or not APT should be continued have often used preoperative APT‐free patients as a control group for the APT continuation group 20,21 . This was thought to be due to the limited number of patients who received APT.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these procedures were in the same intermediate risk group, they could not be said to have the same bleeding risk. In addition, other previous studies on whether or not APT should be continued have often used preoperative APT‐free patients as a control group for the APT continuation group 20,21 . This was thought to be due to the limited number of patients who received APT.…”
Section: Discussionmentioning
confidence: 99%
“…15 When we compared cases with and without anti-thrombotic agents, the incidence of major haemorrhagic complications was significantly higher in the AT group than in the non-AT group despite sufficiently long period of medication discontinuation. Based on the literature, the haemorrhagic complications did not increase after abdominal surgery without withdrawal of aspirin, [15][16][17][18] whereas it could increase after the procedure with heparin bridge. 28,29 In the current study, the assessment by haemorrhagic site showed that the rate of severe haemorrhage from surgical site (anastomosis and peritoneal cavity) was similar in both groups.…”
Section: Ta B L E 5 Comparison Of Patient Characteristics Between Non...mentioning
confidence: 97%
“…Postoperative bleeding after laparoscopic colon resection occurred in approximately 1.1% of cases in a Japanese randomized trial that compared the outcomes of laparoscopic colectomy and laparotomy in colon cancer 15 . Some investigators have reported that the administration of aspirin without cessation during the perioperative period does not increase the haemorrhagic events during and after laparoscopic colorectal surgery 16–18 . However, the risks of thrombotic events after laparoscopic colorectal surgery remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten were observational cohort studies, all of which were retrospective in nature. Concerning the research on the management of patients with prolonged ATT, one study was a multicenter retrospective cohort analysis [ 8 ] and three were analyses using the propensity score matching method [ 6 , 9 , 11 ].…”
Section: Reviewmentioning
confidence: 99%